The Impact of Positive Mood and Future Outlook on English as a Foreign Language Students’ Academic Self-Concept - Zhang, Jingsheng (Frontiers in Psychology, 2022)
Due to the fact that EFL students’ academic self-concept is of high importance for their academic motivation, academic achievement, and L2 success, many investigations have been done to uncover the personal and interpersonal factors that may contribute to students’ academic self-concept. Yet, the emotional and psychological factors have rarely been studied. In addition, no empirical and review study has been carried out to probe into the impact of positive mood and future outlook on English as a foreign language (EFL) students’ academic self-concept. Accordingly, the current review study seeks to illustrate the effects of positive mood and future outlook on EFL students’ academic self-concept. Building upon the principles of positive psychology (PP), the favorable effects of positive mood and future outlook on EFL students’ academic self-concept were thoroughly explained. The educational implications and suggestions for future research are also highlighted.